Drivers of Employee Motivation: Mediating Role of Job Satisfaction - Azeem, Sabeen (2016)
Employee Motivation is a growing area of importance for the Human Resource Departments organizations of all sizes. Managing the workforce efficiently and effectively has become crucial in order to achieve excellent output from the employees which would lead to the attainment of organizational goals. This study aims to understand the influence of multiple motivational factors on employee motivation of employees of Bank A. Additionally, the mediating role of job satisfaction is elaborated which would lead to employee motivation. Furthermore, the research focuses on the differing motivational needs of different positions of employees such as entry level, mid level, and top level employees. The study used both quantitative (survey) and qualitative (interview) methods for data collection. Responses from 265 participants from Bank A were gathered and analyzed using SPSS tool. Additionally, data was collected by conducting an interview from the manager of Bank A. The results show that compensation, work life balance, performance appraisal, job design, and work environment – all have a moderate to strong influence on employee motivation. However, the top ranking motivational factor is different for different employee positions. In spite of quite a number of existing researches done on employee motivation, little research has addressed the most influential motivational factors for employees based on employee position in the organization. The empirical evidence of this study will contribute to the literature by providing a novel perspective on employee motivation.